Gamification of Professional Small Talk: Enhancing Interpersonal English Skills for Vocational Students via Micro-learning Mobile Apps - Hermansyah Hermansyah; Arief Hidayat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aimed to investigate the implementation of a gamified micro-learning mobile application specifically engineered to develop interpersonal English conversational competence among vocational college students. Employing a mixed-methods empirical approach, 120 undergraduate students from Politeknik Unggul LP3M were assigned to either an experimental group utilizing the gamified micro-learning intervention or a control group undergoing conventional teacher-led interpersonal dialogue simulations over a 16-week academic semester. Interpersonal competence was measured quantitatively via standardized pre- and post-tests evaluating pragmatic appropriateness, linguistic fluency, and conversational initiation capabilities, supplemented by physiological and self-reported communication anxiety metrics. Quantitative analyses demonstrated a statistically significant improvement in the experimental group's micro-interaction capabilities (p < 0.01) and an extensive reduction in English communication anxiety levels. Qualitative interviews revealed that gamified rewards, micro-credentials, and spaced-repetition loops lowered the psychological barriers associated with casual L2 interactions. The paper concludes with structural recommendations for incorporating interactive gamified frameworks into vocational General English and ESP pedagogical ecosystems